2014
DOI: 10.1007/s00204-014-1197-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple transcriptomic signature able to predict drug-induced hepatic steatosis

Abstract: It is estimated that only a few marketed drugs are able to directly induce liver steatosis. However, many other drugs may exacerbate or precipitate fatty liver in the presence of other risk factors or in patients prone to non-alcoholic fatty liver disease. On the other hand, current in vitro tests for drug-induced steatosis in preclinical research are scarce and not very sensitive or reproducible. In the present study, we have investigated the effect of well-characterized steatotic drugs on the expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 56 publications
0
32
1
Order By: Relevance
“…The concentrations selected were always subcytotoxic (#IC 10 ), thus avoiding acute necrotic or apoptotic side effects (Benet et al, 2014). Moreover, we have previously shown that in these conditions, the selected steatotic drugs trigger lipid accumulation in HepG2 cells (Benet et al, 2014). We observed that most steatotic drugs (valproate, doxycycline, tetracycline, cyclosporine A, and tianeptine) negatively affected SHP expression (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The concentrations selected were always subcytotoxic (#IC 10 ), thus avoiding acute necrotic or apoptotic side effects (Benet et al, 2014). Moreover, we have previously shown that in these conditions, the selected steatotic drugs trigger lipid accumulation in HepG2 cells (Benet et al, 2014). We observed that most steatotic drugs (valproate, doxycycline, tetracycline, cyclosporine A, and tianeptine) negatively affected SHP expression (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Human hepatoma HepG2 cells were incubated for 24 hours with different drugs previously characterized and classified as nonhepatotoxic, hepatotoxic, phospholipidosic, and steatotic. The concentrations selected were always subcytotoxic (#IC 10 ), thus avoiding acute necrotic or apoptotic side effects (Benet et al, 2014). Moreover, we have previously shown that in these conditions, the selected steatotic drugs trigger lipid accumulation in HepG2 cells (Benet et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further mature the cells, we investigated the role of cAMP signalling, as studies using hepatic cell lines have shown that activation of this pathway induces hepatic gene expression, in part through the induction of the peroxisome proliferator-activated receptor γ co-activator 1α (PGC1A; PPARGC1A -Human Gene Nomenclature Database), a co-activator that functions together with HNF4A to regulate the expression of many genes involved in hepatocyte function (Bell and Michalopoulos, 2006;Arpiainen et al, 2008;Benet et al, 2010;Dankel et al, 2010). Treatment of the aggregates with 8-bromoadenosine-3Ј,5Ј-cyclic monophosphate (8-Br-cAMP), a cell-permeable analogue of cAMP, from days 32 to 44 of culture significantly enhanced the expression of PGC1A (15-fold), G6P (25-fold) and TAT (33-fold) but not that of HNF4A (Fig.…”
Section: Camp Signaling Induces Maturation Of Hescderived Hepatocyte-mentioning
confidence: 99%